2005
DOI: 10.1177/003693300505000306
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an Extreme Sports Event on a District General Hospital

Abstract: We believe that extreme sports events can have considerable impact on small district general hospitals. Additional triage and staffing resources should be utilised and event organisers should anticipate the additional problems they present to the local community. District General Hospitals continue to provide a substantial contribution to the provision of health care for extreme sports within the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…1 Being thrown over the handlebars following sudden deceleration is the most common mechanism of injury and has the most serious results. 4 Most papers agree that orthopaedic injuries are the most commonly sustained, [3][4][5] including fractures and soft tissue injuries. Of the upper limb fractures, fractures of the clavicle is the most common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Being thrown over the handlebars following sudden deceleration is the most common mechanism of injury and has the most serious results. 4 Most papers agree that orthopaedic injuries are the most commonly sustained, [3][4][5] including fractures and soft tissue injuries. Of the upper limb fractures, fractures of the clavicle is the most common.…”
Section: Discussionmentioning
confidence: 99%
“…With the rising popularity of the sport, an increasing number of enthusiasts are involved in exploring new, exciting but treacherous terrain. [1][2][3][4][5] We aimed to review the incidence and produce a breakdown of orthopaedic injuries related to this sport at a regional district general hospital in North of England, that serves a population of 550 000. This enabled us to report in greater detail on patients sustaining complex injuries of the shoulder girdle, involving disruption to the four-bar linkage consisting of disruption of the bony-soft tissue ring of structures namely, clavicle, coracoclavicular ligaments and coracoid linkage ( figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Of those emergency department admissions, 66% required surgical intervention (8). It has been suggested that presentations related to mountain bike competitions in small jurisdictions can have a significant workload impact on healthcare providers and facilities (16). Of those injured, young males are most commonly represented, however females may have a higher propensity for injury (6,9).…”
Section: Introductionmentioning
confidence: 99%
“…The people who exercise regularly might receive better overall long term health benefits [19, 22, 24]. Several researchers also claim that the warm-up and stretching movements is highly important prior to the actual exercise in order to avoid sports-related injuries [2528]. People with sports-related injuries will look for rehabilitative treatments, and may lead to an increased number of outpatient visits.…”
Section: Discussionmentioning
confidence: 99%